ESTIMATIVA DE VOLUME INDIVIDUAL DE MOGNO AFRICANO POR MEIO DE REDES NEURAIS ARTIFICIAIS (RNAS) - BARBA, Mário Sérgio Brandão; FERREIRA, Victória Viédes; SILGUEIRO, João Manoel Lobo Duarte; COUTO, Allan Motta (ANAIS DO ENIC, 2022)
-